Orthopedic iron-magnesium implant and preparation method thereof

By introducing solid solution heterostructure and micro-nano powder mixing into biomedical iron, the problem of traditional metal bone implants cannot be degraded by themselves is solved, and the rapid degradation and high biocompatibility of iron-based bone implants are achieved, and the need for secondary surgery is avoided.

CN119838054APending Publication Date: 2025-04-18HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411859105.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional metal bone implants cannot degrade by themselves and require a secondary surgery to remove, which increases the patient's pain and cost pressure.

Method used

By introducing solid solution heterostructure into biomedical iron, magnesium atoms are solidly dissolved into the iron lattice, improving the corrosion potential and degradation rate of the iron matrix, and forming heterostructures by mixing micro-nano powders, further increasing the instability of the passivation film.

Benefits of technology

The rapid degradation of iron-based bone implants is achieved, the need for secondary surgery is avoided, the pain and medical costs of patients are reduced, and the biocompatibility of the implant is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838054A_ABST
    Figure CN119838054A_ABST
Patent Text Reader

Abstract

The invention relates to an orthopedic iron-magnesium implant and a preparation method thereof, and belongs to the field of manufacturing of dissoluble orthopedic implants. The preparation method of the orthopedic iron-magnesium implant comprises the following steps: step 1, mechanical mixing: equivalently adding iron powder into magnesium powder for 4-8 times, and stirring for 60-70 minutes to form iron-magnesium micron powder; 2, magnesium solid solution, wherein the iron-magnesium micron powder is put into a ball milling tank for solid solution; 3, forming a heterostructure: equivalently adding iron-magnesium nano powder into the iron-magnesium micron powder in the step 1 for 4-6 times, and stirring for 60-70 minutes, wherein the ratio of the iron-magnesium nano powder to the iron-magnesium micron powder is 1: 1; and fourthly, electric spark sintering forming is conducted, specifically, an electric spark sintering process is adopted for curing forming. The method has the beneficial effects that the electrochemical heterogeneity of the alloy is expanded, the corrosion sensitivity of the alloy is improved, the instability of a passive film is improved, and thus the degradation rate of the alloy is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biodegradable medical iron-based bone implant and belongs to the field of manufacturing soluble orthopedic implants. Background Art

[0002] With the frequent occurrence of cases of human bone damage due to traffic and aging, in order to repair damaged bone tissue, suitable bone implant materials are needed to help the bone complete repair. Although traditional metal bone implants (titanium, stainless steel, etc.) have good implantation performance, they will not affect the bone tissue during implantation in human bone tissue, and can provide sufficient support for the bone tissue without damage. However, traditional metal bone implants cannot degrade by themselves and need to be removed in a secondary operation after the bone is completely healed, which increases the patient's pain and cost pressure. In view of the shortcomings of traditional bone implant metals, it is an ideal solution to develop a degradable metal with good implantation performance and no need for secondary surgery to remove.

[0003] Magnesium-based, zinc-based and iron-based metal materials are considered to be three valuable biodegradable implant materials. Among them, the degradation rate of magnesium-based materials is too fast. During the service process, the bone tissue has not yet healed, and the magnesium-based implant loses its supporting performance due to excessive degradation, and the degradation will release excessive hydrogen. Zinc-based materials are insufficient in mechanical properties. Compared with magnesium-based and zinc-based materials, iron-based materials have good mechanical properties, and will not fail or release hydrogen during service. In addition, iron is one of the trace elements in the human body, participating in physiological activities such as oxygen transportation and metabolism, and will not cause serious local or systemic toxicity to the human body. In vivo and in vitro biological experiments have also confirmed this conclusion. However, the degradation rate of iron is slow, so developing a method to accelerate the degradation rate of iron can improve the competitiveness of iron-based bone implants. Summary of the invention

[0004] Based on the problem of slow degradation rate of biomedical iron, the present invention proposes a method for accelerating degradation of solid solution heterostructure. A solid solution heterostructure is introduced into biomedical iron; magnesium atoms are first dissolved into the iron lattice, so that the corrosion potential of the iron matrix will shift negatively, and the overall corrosion driving force will increase. Subsequently, the heterostructure formed by the mixture of micro-nano powders further expands the electrochemical heterogeneity of the iron metal, increases the instability of the passivation film, and thus further increases the degradation rate of the iron metal.

[0005] The orthopedic iron-magnesium implant and the preparation method thereof described in the present invention are prepared by the following technical steps:

[0006] Step 1: Mechanical mixing;

[0007] After the iron powder is dried at a constant temperature, it is added to the magnesium powder in equal amounts in 4-8 times and stirred for 60-70 minutes. During the stirring process, the iron powder is turned upside down to evenly disperse the magnesium powder to form iron-magnesium micron powder;

[0008] Step 2: solid solution of magnesium;

[0009] The iron-magnesium micron powder is placed in a ball mill for solid solution, and an inert gas is used to provide a protective atmosphere during the ball milling process. The mass ratio of the iron-magnesium micron powder to the grinding ball is 1:20, the ball milling speed is 250-350 / min, the ball milling time is 18-38 hours, and cooling is performed for 15 minutes after each ball milling for 1 hour to form iron-magnesium nanopowder;

[0010] Step 3: forming a heterostructure;

[0011] The nano powder after solid dissolving magnesium is screened, and then the iron-magnesium nano powder is added to the iron-magnesium micro powder in step 1 in equal amounts in 4-6 times and stirred for 60-70 minutes, turning upside down during the stirring process to evenly disperse the micro powder, wherein the iron-magnesium nano powder: iron-magnesium micro powder = 1:1;

[0012] Step 4: electric spark sintering;

[0013] The electric spark sintering process is used for solidification and molding; the iron-magnesium micro-nano mixed powder after step three is solidified and molded by the electric spark sintering process, the electric spark sintering temperature is 540-660 degrees, the pressure is 1.2-2.8KN, and during the sintering process, the sintering chamber is kept in a vacuum state and a protective atmosphere is provided.

[0014] Furthermore, in the orthopedic iron-magnesium implant and the preparation method thereof, the iron-magnesium micron powder has a size of 65-80 um and is spherical.

[0015] Furthermore, in the orthopedic iron-magnesium implant and the preparation method thereof, the iron-magnesium nanopowder is in the form of flakes.

[0016] The orthopedic iron-magnesium implant and the preparation method thereof described in the present invention include the following components by mass percentage:

[0017] Magnesium 1-50%, preferably 2-9wt.%, more preferably 3wt.%;

[0018] In the present invention, electric spark sintering utilizes pulse energy, discharge pulse pressure and instantaneous high temperature generated by Joule heat to achieve powder sintering, which can quickly complete powder melting and solidification molding at a temperature lower than the melting point of the material. It has the advantages of uniform heating, fast heat conduction and short sintering time. It is an advanced low-temperature rapid densification molding technology.

[0019] Magnesium is an effective bone repair material with good biological activity. It has biocompatibility and biosafety in medical fields such as bone defects, and has wide application value and prospects. In the present invention, the melting point of Fe (1538 degrees) is higher than 660 degrees, and the melting temperature of magnesium is lower than 660 degrees, so magnesium will volatilize before the iron is fully melted. In order to retain the complete magnesium, the iron is fully melted. The iron-magnesium biological bone implant is quickly formed by electric spark sintering. The sintering temperature is lower than the melting point of magnesium, which prevents magnesium from separating from the iron matrix at high temperature. At the same time, the electric spark sintering time is fast and short, which avoids the disadvantages of long-term heating of iron and magnesium in the traditional smelting process and destruction of the solid solution structure; during the sintering process, no obvious flow of liquid iron is generated, and the size of the iron-magnesium bone implant can be adjusted by a graphite mold, which helps to prepare large sections of iron-magnesium bone implants conveniently and quickly.

[0020] The content of magnesium in the present invention needs to be strictly controlled. Too much magnesium addition will cause uneven mixing in the iron matrix, and the dense distribution of nano magnesium particles makes it difficult to form a good transition with the iron-based metal flux. On the other hand, too many magnesium particles will increase the average thermal expansion coefficient difference between the iron-based alloy and the magnesium particles. Therefore, in the rapid solidification process, excessive thermal stress will produce cracks. Thereby the mechanical mixing of iron powder and magnesium powder, magnesium solid solution, and heterogeneous structure process steps are particularly important, including stirring time, ball milling time, ball-to-material ratio, etc.; if the amount of magnesium added is too little, the improvement effect of the degradation performance of the iron matrix is ​​limited, and it is difficult to accelerate the degradation effect, so it is necessary to reasonably select the powder ratio.

[0021] The electric spark sintering process has a great influence on the molding performance of medical iron-based bone implants. If the electric spark sintering temperature is low, the mixed powder is difficult to melt completely, the molded sample contains powder particles and is soft, and the molded sample is degraded and has poor integrity; if the electric spark sintering pressure is small, the density is greatly affected and the density performance is low.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) In the present invention, the magnesium is safe and convenient in clinical application, has good biocompatibility, is an effective bone repair material, and helps promote bone repair.

[0024] (2) The iron-based bone implant of the present invention is composed of an iron-magnesium biological bone implant, which is biodegradable, thereby avoiding the disadvantages of inert metal implants existing in the body for a long time and requiring secondary surgery for removal, and is expected to avoid the potential risk of complications.

[0025] (3) In the present invention, when magnesium with a low electrode potential dissolves into the iron lattice, the corrosion potential of the substrate shifts negatively and the overall degradation rate accelerates.

[0026] (4) In the present invention, the mixing of micro-nanoparticles in the heterogeneous structure expands the electrochemical heterogeneity of the alloy, which not only increases the corrosion sensitivity of the alloy but also increases the instability of the passivation film, thereby increasing the degradation rate of the alloy.

[0027] (5) In the present invention, the electric spark sintering molding method is simple and reliable. The electric spark sintering can quickly mold iron-based bone implants. The molding process is simple, saving time and labor. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Morphology of Fe-Mg micron powder and Fe-Mg nano powder;

[0029] Figure 2 XRD showed that magnesium was in solid solution;

[0030] Figure 3 Surface micromorphology of iron-based bone implants with Fe-Mg heterostructures;

[0031] Figure 4 Surface degradation rate of iron-based bone implants with iron-magnesium heterostructures;

[0032] Figure 5 Rapid degradation morphology of iron-based bone implants with iron-magnesium heterostructures;

[0033] Figure 6 Mechanical properties of Comparative Example 1; DETAILED DESCRIPTION

[0034] Example 1

[0035] After the iron powder is dried at a constant temperature, it is added to the magnesium powder in 8 equal portions and stirred for 60 minutes. During the stirring process, the iron powder is turned upside down to evenly disperse the magnesium powder to form iron-magnesium micron powder. Figure 1 a, wherein iron and magnesium are prepared in a mass ratio of 97:3; the iron and magnesium micron powders are placed in a ball mill to form a solid solution, such as Figure 2 Inert gas is used to provide a protective atmosphere during the ball milling process. The mass ratio of iron-magnesium micron powder to grinding balls is 1:20, the ball milling speed is 300 / rpm, the ball milling time is 32 hours, and cooling is performed for 15 minutes after every 60 minutes of ball milling to form iron-magnesium nanopowder. Figure 1 b. Screen the iron-magnesium nanopowder, then add the iron-magnesium nanopowder to the iron-magnesium micron powder in 6 equal amounts and stir for 60 minutes. During the stirring process, turn the powder upside down to evenly disperse the micron powder, wherein the iron-magnesium nanopowder: iron-magnesium micron powder = 1:1; use the electric spark sintering process to solidify and shape; use the electric spark sintering process to solidify and shape the iron-magnesium micro-nano mixed powder to form a heterogeneous structure, such as Figure 3 The electric spark sintering temperature is 600 degrees and the pressure is 2.2KN. During the sintering process, the sintering chamber maintains a vacuum state and provides a protective atmosphere.

[0036] Implementation effect:

[0037] The medical iron-based bone implant prepared by this method has a molding diameter of 10 mm and a height of 7 mm. The iron-magnesium solid solution is not destroyed. The medical iron-based bone implant has good overall molding performance, flat molding, smooth surface, and no obvious defects such as warping. Electrochemical degradation rate is as high as 0.58 mm / y. Figure 4 , the immersion test found that the corrosion layer became thicker, such as Figure 5 .

[0038] Example 2

[0039] After the iron powder is dried at a constant temperature, it is added to the magnesium powder in equal amounts in 7 times and stirred for 50 minutes. During the stirring process, the magnesium powder is turned upside down to evenly disperse the magnesium powder to form iron-magnesium micron powder, wherein iron and magnesium are prepared in a mass ratio of 99:2; the iron-magnesium micron powder is placed in a ball mill for solid solution, and an inert gas is used to provide a protective atmosphere during the ball milling process. The mass ratio of iron-magnesium micron powder to grinding ball is 1:20, the ball milling speed is 280 rpm, the ball milling time is 26 hours, and the ball milling is cooled for 10 minutes after every 50 minutes of ball milling to form iron-magnesium nano powder; the iron-magnesium nano powder is screened, and then the iron-magnesium nano powder is added to the iron-magnesium micro powder in 6 equal amounts and stirred for 60 minutes. During the stirring process, the powder is turned upside down to evenly disperse the micro powder, wherein the iron-magnesium nano powder: iron-magnesium micro powder = 1:1; the electric spark sintering process is used for solidification and molding; the iron-magnesium micro-nano mixed powder is solidified and molded by the electric spark sintering process, the electric spark sintering temperature is 580 degrees, the pressure is 1.8KN, and during the sintering process, the sintering chamber is kept in a vacuum state and a protective atmosphere is provided.

[0040] Implementation effect: The medical iron-based bone implant prepared by this method has a molding diameter of 10mm and a height of 8mm. The overall molding performance of the medical iron-based bone implant is good, the upper and lower layers in the microstructure are well bonded, there is no obvious cracking phenomenon, and there are no obvious large shrinkage holes and cracks. Compared with iron, its corrosion potential shifts negatively, the current density increases, and the corrosion driving force increases; the immersion experiment found that the corrosion is faster.

[0041] Example 3

[0042] After the iron powder is dried at a constant temperature, it is added to the magnesium powder in equal amounts in 6 times and stirred for 50 minutes. During the stirring process, the magnesium powder is turned upside down to evenly disperse the magnesium powder to form iron-magnesium micron powder, wherein iron and magnesium are prepared in a mass ratio of 92:8; the iron-magnesium micron powder is placed in a ball mill for solid solution, and an inert gas is used to provide protection during the ball milling process. The mass ratio of iron-magnesium micron powder to grinding ball is 1:20, the ball milling speed is 250 rpm, the ball milling time is 25 hours, and the ball milling time is 10 minutes. After each 40 minutes of ball milling, cooling is performed to form iron-magnesium nano powder; the iron-magnesium nano powder is screened, and then the iron-magnesium nano powder is added to the iron-magnesium micro powder in equal amounts in 5 times and stirred for 60 minutes. During the stirring process, the powder is turned upside down to evenly disperse the micro powder, wherein the iron-magnesium nano powder: iron-magnesium micro powder = 1:1; the electric spark sintering process is used for solidification and molding; the iron-magnesium micro-nano mixed powder is solidified and molded by the electric spark sintering process, the electric spark sintering temperature is 540 degrees, the pressure is 1.2KN, and during the sintering process, the sintering chamber is kept in a vacuum state and a protective atmosphere is provided.

[0043] Implementation effect: The medical iron-based bone implant prepared by this method has a molding diameter of 10 mm and a height of 8 mm. The overall molding performance of the medical iron-based bone implant is good, the upper and lower layers in the microstructure are well bonded, there is no obvious cracking phenomenon, and there are no obvious large shrinkage holes and cracks. The immersion experiment shows that the corrosion products on the surface of the implant become thicker.

[0044] Comparative Example 1

[0045] The other conditions are the same as those in Example 1, except that: iron powder and magnesium powder are weighed at a mass ratio of 60:40 to obtain a medical iron-based bone implant. Electrochemical tests show that the iron-based implant has severe local corrosion, and the obtained medical iron-based bone implant has poor overall molding performance, many defects on the surface, and reduced mechanical properties compared with pure iron. Figure 6 .

[0046] Comparative Example 2

[0047] The other conditions are consistent with those in Example 1, except that: a spherical iron-magnesium mixed powder with a powder particle size of 65-80 microns is placed in a grinding mortar and mechanically mixed for 8 minutes to obtain an iron-magnesium micron powder, which is then mixed with an iron-magnesium nanopowder that has been ball-milled for 26 hours to obtain a medical iron-based bone implant. After sintering, it was found that the surface gloss was uneven, part of the surface fell off, the electric spark sintering performance was poor, and a scanning electron microscope found that the magnesium powder particles were not evenly dispersed in the iron matrix, and agglomeration occurred.

[0048] Comparative Example 3

[0049] The other conditions were consistent with those in Example 1, except that the pressure applied during the electric spark sintering process was 0.2 kN, the holding time was 4 minutes, and the medical iron-based implant had poor molding quality, lacked overall structural integrity, and had poor densification performance.

[0050] Comparative Example 4

[0051] The other conditions are consistent with those in Example 1, except that the temperature applied during the electric spark sintering process is 240 degrees, the holding time is 5 minutes, and the applied pressure is 2.1 kN. After sintering, it is observed that the medical iron bone implant cannot be sintered into a shape, and a dense sintered body cannot be produced. This indicates that the medical iron-based bone implant cannot be sintered densely, cannot become a qualified bone implant, and has poor forming performance.

[0052] It can be seen from Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 that the components and preparation process of the present invention are an organic whole, and when any one or several key parameters are not within the protection scope of the present invention, the effect is significantly reduced. By comparing the internal structure of Example 1 of the present invention with Example 2 and Example 3, it is found that the preferred embodiment of the present invention has an unexpected effect.

Claims

1. An orthopedic iron-magnesium implant and a preparation method thereof, characterized in that; The method comprises the following preparation steps: Step 1 Mechanical mixing: After the iron powder is dried at a constant temperature, it is added to the magnesium powder in equal amounts in 4-8 times and stirred for 60-70 minutes. During the stirring process, the iron powder is turned upside down to evenly disperse the magnesium powder to form iron-magnesium micron powder; Step 2: Magnesium solid solution: The iron-magnesium micron powder is placed in a ball mill for solid solution, and an inert gas is used to provide a protective atmosphere during the ball milling process. The mass ratio of the iron-magnesium micron powder to the grinding ball is 1:20, the ball milling speed is 250-350 / min, the ball milling time is 18-38 hours, and cooling is performed for 15 minutes after each ball milling for 1 hour to form iron-magnesium nanopowder; Step 3: Forming a heterostructure: The nano powder after solid dissolving magnesium is screened, and then the iron-magnesium nano powder is added to the iron-magnesium micro powder in step 1 in equal amounts in 4-6 times and stirred for 60-70 minutes, turning upside down during the stirring process to evenly disperse the micro powder, wherein the iron-magnesium nano powder: iron-magnesium micro powder = 1:1; Step 4: Electric spark sintering: The electric spark sintering process is used for solidification and molding; the iron-magnesium micro-nano mixed powder after step three is solidified and molded by the electric spark sintering process, the electric spark sintering temperature is 540-660 degrees, the pressure is 1.2-2.8KN, and during the sintering process, the sintering chamber is kept in a vacuum state and a protective atmosphere is provided.

2. An orthopedic iron-magnesium implant and a preparation method thereof according to claim 1, characterized in that: The size of the iron-magnesium micron powder is 65-80um and is spherical.

3. An orthopedic iron-magnesium implant and a preparation method thereof according to claim 1, characterized in that: The iron-magnesium nano powder is in the form of flakes.

4. The orthopedic iron-magnesium implant and the preparation method thereof according to claim 1, characterized in that: The mass percentage of the magnesium powder is 1-50%.

5. The orthopedic iron-magnesium implant and the preparation method thereof according to claim 1, characterized in that: The mass percentage of the magnesium powder is 2-9%.

6. The orthopedic iron-magnesium implant and the preparation method thereof according to claim 1, characterized in that: The mass percentage of the magnesium powder is 3%.